Effectiveness Of Combination Aloe Vera Extract With Calcium Hydroxide Against Enterococcus Faecalis Bacteria - Styaningrum, Yunita; Ardlina, Nira; Samara, Samara (Odonto : Dental Journal, 2024)
Background: Enterococcus faecalis bacteria is widely regarded as the leading cause of root canal treatment failure due to its ability to survive in extreme environments. The use of herbal plants such as Aloe vera can be used as an intracanal medicament because it has been proven to have an antibacterial property. Calcium hydroxide (aqueous) intracanal medication mixed with Aloe vera is able to inhibit the growth of Enterococcus faecalis, to see the antibacterial effectiveness of the combination of Aloe vera extract with calcium hydroxide paste (aqueous) as an intracanal medicament against Enterococcus faecalis bacteria. Methods: This experimental research was conducted in the laboratory with a post-test control design. The number of research samples used was 30 pieces. The maceration method was used to make the Aloe vera extract and the Mc Farland turbidity standard was adjusted for Enterococcus faecalis bacterial growth. Then to determine the antibacterial effectiveness, the inhibition zone which is the area around the well that is clear and smaller in diameter than the well, was measured using a digital caliper. Results: Statistical tests were performed using the Kruskal Wallis test and obtained a significance number of 0,000 (p <0.05) then the Mann Whitney test was carried out to obtain a significance number of 0.000 (p <0.05). Conclusions: According to the results of this study, calcium hydroxide paste was less effective at killing Enterococcus faecalis bacteria than a mixture of calcium hydroxide and aloe vera extract.